Lovesickness: Medieval Literary Representations of a Medical Discourse - Marian Elizabeth Polhill (2016)
Abstract for article and longer project on literary representations of the medical discourse of lovesickness, with particular attention to gender and violence. Part of the project was presented at the Nineteenth Biennial International Congress of the New Chaucer Society held in Reykjavik, Iceland in 2014, and is currently being prepared for submission to an open access journal.